Newly qualified professional nurses’ experiences of mentorship in community health care services - Lekhuleni, M. E. (My University, 2014)
The purpose of this study was to explore and describe the newly qualified professional nurses (NQPNs) experiences of mentorship in community health care services. A qualitative-phenomenological design was used. Focus group interview was done to collect data from NQPNs employed in the primary health care services and community hospitals in Limpopo Province. The study was guided by Orem’s theory of self-care deficit. The study findings revealed that NQPNs experienced self-care deficiencies regarding the performance of specific competencies related to dealing with psychiatry, midwifery practices and community health. The NQPNs also expressed poor adaptation in the organizational and health practice cultures and low interaction with the community they serve. The study came up with recommendations related to adaptation/adjustment, health and nursing practice culture, development of skills competencies, improvement of good relationships between NQPNs and community and the development of mentorship model.
Article published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:2 (June), 2014, pp. 378-394.
Keywords: Newly qualified professional nurses; Mentorship; Nurses -- South Africa; Community health nurses; Nurses -- In-service training